2009
DOI: 10.1248/jhs.55.319
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of DNA Conformational Change Induced by Rearrangement of Copper-coordination Geometry in Oxidative DNA Damages Caused by Copper and Dopamine

Abstract: Oxidative DNA damages involve reductionoxidation reactions between certain metals and compounds, and result in genetic abnormalities leading to diseases including cancer and neurodegenerative disorders. Here, we report that DNA damages mediated by combination of a neurotransmitter dopamine and copper accompany a unique DNA conformational change. Copper(II) [Cu(II)] was shown as bound to consecutive guanines (G-G) of DNA, by demonstrating the G-G selective inhibition of restriction enzymes. When dopamine was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Cu(II) is closely located to DNA, and its reduced form Cu(I) tightly binds to DNA and introduces a conformational change. 24) The bound Cu(I) anchors the H 2 O 2 that attacks DNA by forming a DNA-Cu(I)-OOH complex. 16) In contrast, Fe(III)-NTA provides hydroxyl radicals far from DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Cu(II) is closely located to DNA, and its reduced form Cu(I) tightly binds to DNA and introduces a conformational change. 24) The bound Cu(I) anchors the H 2 O 2 that attacks DNA by forming a DNA-Cu(I)-OOH complex. 16) In contrast, Fe(III)-NTA provides hydroxyl radicals far from DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This Cu reduction and subsequent ROS production together with dissolved oxygen induce oxidative damage and conformational changes in DNA strand, as detected by CD measurement. DNA conformational changes are induced by rearrangement of the copper-coordination geometry in DNA through Cu(II) reduction to Cu(I) (Ando et al 2009). In contrast to Cu, iron yielded no detectable changes in the CD spectra of treated DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is present in the nucleus and plays a role in maintaining higher order DNA structure (Bryan et al 1981;Dijkwel and Wenink 1986). We reported previously that Cu(II) selectively binds to consecutive guanine sequences of purified DNA and that DNA conformation is altered by the combination of dopamine and transition metals such as copper (Ando et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different study, it was found that dopamine quenches excited singlet and triplet states of riboflavin [15,16]. Furthermore, dopamine may break a DNA strand in the presence of Cu ion [14,17].…”
Section: Introductionmentioning
confidence: 99%